A prática da integralidade : contos (com) sentidos - Mattanó, Luanna Del Carmen Barbosa (2013)
The Comprehensiveness, one of the guidelines of the National Health System, consists in a refusal of reductionism and objectification of the subject and imposes dialogue in intersubjective relationship. It's battle flag, mobilization and exercise of humanity and is linked to the constitution of meaning for health professionals as a value. The value gives meaning to the world, and through him, choices, paths, practices and objectives of the action are defined. Thus, the practices are routed from the values established subjectively through appreciation and revaluation of everyday experiences. There is an inseparability between value and practice of completeness. The construction of reality integral enables up by exercising everyday professional practices, and through continuous learning, combined with openness to dialogue between various professionals and the community. This research aimed to analyze the practices of health professionals, seeking to understand how exercise the comprehensiveness. Analyzed from the dialogue with workers, the ways, strategies and difficulties in consolidating the practice of comprehensiveness in everyday life. We conducted six focus group sessions and reading your transcript we have chosen three themes highlighted by the Association of Ideas map proposed by Spink (1999). From them we built three stories that illustrate the opinions and ways of experiencing the workers. The stories, such as stories, allow a better approximation of reality, allowing the reader learns all aspects present in situations. The analysis highlights the lack of dialogue, the routine, the need to meet targets based on procedures and the concept of health as absence of disease as the main obstacles to the achievement of comprehensiveness. In contrast, we point out that interdisciplinarity, the values humanized, health promotion and training enable and strengthen comprehensive practices.